An Integrated Framework to Achieve Interoperability in Person-Centric Health Management - Fabio Vergari; Tullio Salmon Cinotti; Alfredo D'Elia; Luca Roffia; Guido Zamagni; Claudio Lamberti (International Journal of Telemedicine and Applications, 2011)
The need for high-quality out-of-hospital healthcare is a known socioeconomic problem. Exploiting ICT's evolution, ad-hoc telemedicine solutions have been proposed in the past. Integrating such ad-hoc solutions in order to cost-effectively support the entire healthcare cycle is still a research challenge. In order to handle the heterogeneity of relevant information and to overcome the fragmentation of out-of-hospital instrumentation in person-centric healthcare systems, a shared and open source interoperability component can be adopted, which is ontology driven and based on the semantic web data model. The feasibility and the advantages of the proposed approach are demonstrated by presenting the use case of real-time monitoring of patients' health and their environmental context.